Bacterial lipopolysaccharide induces apoptosis in the trout ovary - Krasnov Aleksei; Tort Lluis; Acerete Laura; Mas Mario; Montserrat Nuria; MacKenzie Simon; Goetz Frederick W; Planas Josep V (BMC, 2006)
Abstract Background In mammals it is well known that infections can lead to alterations in reproductive function. As part of the innate immune response, a number of cytokines and other immune factors is produced during bacterial infection or after treatment with lipopolysaccharide (LPS) and acts on the reproductive system. In fish, LPS can also induce an innate immune response but little is known about the activation of the immune system by LPS on reproduction in fish. Therefore, we conducted studies to examine the in vivo and in vitro effects of lipopolysaccharide (LPS) on the reproductive function of sexually mature female trout. Methods In saline- and LPS -injected brook trout, we measured the concentration of plasma steroids as well as the in vitro steroidogenic response (testosterone and 17alpha-hydroxyprogesterone) of ovarian follicles to luteinizing hormone (LH), the ability of 17alpha,20beta-dihydroxy-4-pregnen-3-one to induce germinal vesicle breakdown (GVBD) in vitro, and that of epinephrine to stimulate follicular contraction in vitro. We also examined the direct effects of LPS in vitro on steroid production, GVBD and contraction in brook trout ovarian follicles. The incidence of apoptosis was evaluated by TUNEL analysis. Furthermore, we examined the gene expression pattern in the ovary of saline- and LPS-injected rainbow trout by microarray analysis. Results LPS treatment in vivo did not affect plasma testosterone concentration or the basal in vitro production of steroids, although a small but significant potentiation of the effects of LH on testosterone production in vitro was observed in ovarian follicles from LPS-treated fish. In addition, LPS increased the plasma concentration of cortisol. LPS treatment in vitro did not affect the basal or LH-stimulated steroid production in brook trout ovarian follicles. In addition, we did not observe any effects of LPS in vivo or in vitro on GVBD or follicular contraction. Therefore, LPS did not appear to impair ovarian steroid production, oocyte final maturation or follicular contraction under the present experimental conditions. Interestingly, LPS administration in vivo induced apoptosis in follicular cells, an observation that correlated with changes in the expression of genes involved in apoptosis, as evidenced by microarray analysis. Conclusion These results indicate that female trout are particularly resistant to an acute administration of LPS in terms of ovarian hormone responsiveness. However, LPS caused a marked increase in apoptosis in follicular cells, suggesting that the trout ovary could be sensitive to the pro-apoptotic effects of LPS-induced inflammatory cytokines.